Mixed methods analysis of an interdisciplinary intervention to promote balance confidence in lower limb prosthesis users - Rosenblatt, Noah J.; Schneider, Kristin L.; Miller, Steven A.; Hagopian, Kavork; Hagg, Sarah; Reddin, Christopher; Churchill, Rachel; Dams, Gregory M.; Calamari, John E.; Stachowiak, Aaron; Major, Matthew J. (Frontiers in Rehabilitation Sciences, 2025)
IntroductionLow balance confidence, i.e., low self-perception in ones' ability to maintain balance while performing activities, is prevalent among lower limb prostheses users (LLPUs) and can affect community participation and quality of life (QoL). Although low balance confidence can manifest from poor function, it also depends on one's beliefs in their abilities to engage in activities, which need not reflect actual abilities. Increasing low balance confidence and associated participation limitations requires approaches that address its' physical and psychological underpinnings.MethodsA randomized controlled trial was conducted to evaluate the initial effectiveness of a multicomponent intervention to target balance confidence in LLPU. Nineteen adults with ≥6-months experience using a prosthesis for unilateral, transtibial amputation, and with low balance confidence (Activities-specific Balance Confidence (ABC) scale scores ≤ 80) completed up to eight intervention sessions following an established protocol, which integrated physical therapy exercises (primarily virtual reality active gaming) and cognitive behavioral therapy strategies, or eight weeks of at home-seated exercises. Outcome measures, collected before randomization, and 0- and 16- weeks after completing the intervention/at-home exercises, addressed four domains: (i) balance confidence—the ABC scale, modified Gait Self Efficacy scale and the Fear of Falling Avoidance Behavior Questionnaire; (ii) community participation—sections of the 36-Item Short Form Survey, sections of the Community Reintegration of Injured Servicemembers scale, the Frenchay Activity Index and step counts; (iii) QoL—the wellbeing scale of the Prosthetic Evaluation Questionnaire; and (iv) function—the Berge Balance Sale and the L-Test of walking. Statistical tests compared baseline and post-training assessment scores between groups, and individual responsiveness was evaluated by comparing change scores to minimum detectable change (MDC).ResultsOverall, results support the initial efficacy of the intervention, with at least one outcome in 3-of-4 domains (balance confidence, community participation and functional mobility) showing strong, significant group-level effects, or individual-level effects (>30% of participants having changes > MDC). Moreover, semi-structured exit interviews suggest participants perceived benefit from the intervention.DiscussionIntegrating physical therapy exercises with cognitive behavioral therapy strategies to simultaneously address physical underpinnings and maladaptive cognitions around low balance confidence can meaningfully improve balance and walking confidence, as well as community participation. To the best of our knowledge the current study is the first to evaluate an intervention to specifically target balance confidence in LLPUs. Clinical Trial Registrationclinicaltrials.gov, identifier NCT03411148.